2016
DOI: 10.1115/1.4032496
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Integrated Circuit With Embedded Microfluidic Cooling: Technology, Thermal Performance, and Electrical Implications

Abstract: This paper reports on novel thermal testbeds with embedded micropin-fin heat sinks that were designed and microfabricated in silicon. Two micropin-fin arrays were presented, each with a nominal pin height of 200 μm and pin diameters of 90 μm and 30 μm. Single-phase and two-phase thermal testing of the micropin-fin array heat sinks were performed using de-ionized (DI) water as the coolant. The tested mass flow rate was 0.001 kg/s, and heat flux ranged from 30 W/cm2 to 470 W/cm2. The maximum heat transfer coeffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…They designed and microfabricated two micropin-fin arrays for experiments. The results obtained from the two testbeds were compared and analyzed, and showed that the density of micropin-fins has a significant impact on thermal performance [ 55 ].…”
Section: Thermal Models Characteristics and Transmissions In Micmentioning
confidence: 99%
“…They designed and microfabricated two micropin-fin arrays for experiments. The results obtained from the two testbeds were compared and analyzed, and showed that the density of micropin-fins has a significant impact on thermal performance [ 55 ].…”
Section: Thermal Models Characteristics and Transmissions In Micmentioning
confidence: 99%
“…Among them, the embedded heat sink cooling technology shortens the heat dissipation path of the chip from “chip-TIM-packing-shell-TIM-heat sink” to “chip-heat sink-working fluid”, that is, it bypasses the chip packaging and directly cools the hotspot of the chip [ 16 ], effectively coping with the more severe heat dissipation challenge caused by the surge during chip integration. Therefore, the research on embedded liquid cooling heat sinks has aroused extensive interest from many scholars, both at home and abroad [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the silicon based microfluidic devices, especially those with wide and/or deep microchannels like for instance integrated circuits for cooling or gas chromatography, are still sealed with wafer bonding techniques [1,2]. This cumbersome method limits miniaturization and further system integration possibilities.…”
Section: Introductionmentioning
confidence: 99%